2017
DOI: 10.1161/circheartfailure.116.003780
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Reclassification of Risk for Incidence of Heart Failure

Abstract: Background— It is well established that cardiorespiratory fitness (CRF) is inversely associated with cardiovascular and all-cause mortality. However, little is known regarding the association between CRF and incidence of heart failure (HF). Methods and Results— Between 1987 and 2014, we assessed CRF in 21 080 HF-free subjects (58.3±11 years) at the Veterans Affairs Medical Centers in Washington, DC, and Palo Alto, CA. Subjects were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 45 publications
(39 reference statements)
4
29
0
1
Order By: Relevance
“…In the current study, the 16% lower risk per 1 MET increase in CRF is similar to that reported by these previous studies . Collectively, the salient clinical implications of the present findings and previous reports is that moderate levels of physical activity that lead to at least moderate increases in CRF can potentially play an important role in the prevention of HF. Failing to meet moderate CRF levels has at least equally, if not more deleterious consequences as traditional co‐morbidities associated with HF.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the current study, the 16% lower risk per 1 MET increase in CRF is similar to that reported by these previous studies . Collectively, the salient clinical implications of the present findings and previous reports is that moderate levels of physical activity that lead to at least moderate increases in CRF can potentially play an important role in the prevention of HF. Failing to meet moderate CRF levels has at least equally, if not more deleterious consequences as traditional co‐morbidities associated with HF.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported higher rates of hospitalization for HF in the least‐fit quartile of subjects vs. the highest‐fit quartile and 17–21% lower risks of HF hospitalization and HF incidence for each 1 MET increment in CRF . In the current study, the 16% lower risk per 1 MET increase in CRF is similar to that reported by these previous studies .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations